2016
DOI: 10.1038/jp.2016.26
|View full text |Cite
|
Sign up to set email alerts
|

Predicting death or extended length of stay in infants with congenital diaphragmatic hernia

Abstract: Six variables predicted death or LOS ⩾109 days in this large, contemporary cohort with CDH. These results can assist in risk adjustment for comparative benchmarking and for counseling affected families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…About one-third of infants with CDH require extracorporeal life support (ECLS), representing the most severe lesions [ 3 ]. While the overall survival rate for isolated CDH ranges from 50–80%, infants requiring ECLS have worse survival rates, with almost six times increased odds of mortality [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…About one-third of infants with CDH require extracorporeal life support (ECLS), representing the most severe lesions [ 3 ]. While the overall survival rate for isolated CDH ranges from 50–80%, infants requiring ECLS have worse survival rates, with almost six times increased odds of mortality [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Congenital diaphragmatic hernia (CDH) occurs in~1 in 3000 live births and has a mortality rate between 20-40% [1][2][3][4]. Prenatal predictors of survival, based on ultrasound and magnetic resonance imaging findings [5,6], can aid in prenatal counselling of families regarding survival and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] A previously published study shows that a diagnosed BSI is one factor that predicts mortality or prolonged length of stay. [15] In this study, the incidence of nosocomial infection, length of stay and total medical expenses of hospitalized patients in the STG were signi cantly higher than those of patients in the NTG; further analysis found that the total intubation time, length of stay and cost of children with nosocomial infection were higher than those in the nosocomial infection-free group. It was shown that the occurrence of nosocomial infection is associated with prolonged hospital stay.…”
Section: Discussionmentioning
confidence: 47%